Calculating the Economic Value Generated by natural and Heritage Areas: the Valuing Places Toolkit - Wood, David; Jones, Tod; Carlsen, Jack (Wildlife Tourism Australia, 2006)
In the five years to 2004, ninety percent of Australians have participated in a nature-based activity and in 2004 alone eighty percent of international visitors participated in activities involving the outdoors and nature. Despite these figures, managers have struggled to demonstrate the economic benefits of natural and heritage places since they capture very little of the tourist revenue. Under-resourced management is potentially devastating given the importance of these places to attracting tourists and the potential damage of growing visitor numbers. Calculating the amount that tourists spend while they are visiting natural and heritage areas demonstrates the economic importance of natural areas and provides a strong argument for better resourcing natural and heritage area management.In this paper, we demonstrate the Valuing Places Toolkit, a new tool for calculating the economic contribution of natural and heritage areas to regional economies. The basis of the Valuing Places Toolkit is longitudinal research into tourism planning in the Gascoyne region of Western Australia. The Valuing Places Toolkit equips users to quickly calculate the amount that tourists spend in a region while visiting national parks and heritage sites. During the presentation, we will demonstrate the quick calculation of tourist expenditure for the Southern Forest tourist region in Western Australia. The Valuing Places Toolkit also provides users with a survey tool for collecting more detailed data about tourist expenditure in a region and supplies information about professional data analysis and reporting services. The methods used in the Valuing Places Toolkit have been developed collaboratively with CALM (Conservation and Land Management) and the Western Australian Treasury. Data generated using these methods has already been influential in procuring increased funding for the Ningaloo Marine Park.